The Speaking English Material Needs of Engineering Students for the English Club Program: An ESP Analysis - Reski Ramadhani; Hilmi Aulawi; Ridwan Setiawan; Sri Rahayu (Pusat Studi Pendidikan Bahasa dan Sastra Inggris, 2023)
Needs analysis as the basis of English for specific purposes (ESP) is deemed crucial to identify the target materials or languages used in the teaching-learning process and to design an effective curriculum. This study aims to investigate engineering students' needs for English-speaking materials in the English club program of one private university in Garut. To address the result of ESP analysis, the researchers used the descriptive qualitative method with questionnaires and interviews as the instruments. The need analysis result revealed that the English learning goal for the students in the English club program is to communicate actively in English. Their interest in learning English in this program is to improve their speaking ability to support their formal study as university students since it influences their academic performance and prepares them to fulfill the demands of job requirements in the future. Most students consider that the materials they need to learn are related to job life, academic purposes as engineering students, and social interaction. The result also suggests that the module created by the tutor for the English club program should focus on topics related to job life that are relevant to the current situation.